2012
DOI: 10.5194/acp-12-4951-2012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medium range transport of particles from nucleation burst on particle number concentration within the urban airshed

Abstract: Abstract. An elevated particle number concentration (PNC) observed during nucleation events could play a significant contribution to the total particle load and therefore to the air pollution in the urban environments. Therefore, a field measurement study of PNC was commenced to investigate the temporal and spatial variations of PNC within the urban airshed of Brisbane, Australia. PNC was monitored at urban (QUT), roadside (WOO) and semi-urban (ROC) areas around the Brisbane region during 2009. During the morn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…For cluster and intermediate ions, relatively weak directional dependency was observed compared to that for large ions. In previous studies, anthropogenic pollution (including local vehicle and industrial emissions) was found to be dominant when southwesterly and northeasterly winds prevailed (Cheung et al, 2011(Cheung et al, , 2012. The results of this study further suggested that higher large ion concentrations were also associated with the southwest/ northeast directions, whereas the relatively uniform concentrations for cluster and intermediate ions were attributed to neutral ion production, such as the ionization of air molecules by cosmic rays.…”
Section: Overall Resultssupporting
confidence: 33%
“…For cluster and intermediate ions, relatively weak directional dependency was observed compared to that for large ions. In previous studies, anthropogenic pollution (including local vehicle and industrial emissions) was found to be dominant when southwesterly and northeasterly winds prevailed (Cheung et al, 2011(Cheung et al, , 2012. The results of this study further suggested that higher large ion concentrations were also associated with the southwest/ northeast directions, whereas the relatively uniform concentrations for cluster and intermediate ions were attributed to neutral ion production, such as the ionization of air molecules by cosmic rays.…”
Section: Overall Resultssupporting
confidence: 33%
“…An origin from the industrial zone is plausible. As already reported, a large coal-fired power plant and an oil refinery are located in the industrial area of Porto Marghera and both installations are potential sources of particles in the nucleation range (Nielsen et al, 2002;Liu et al, 2010;Cheung et al, 2012) and SO 2 . Emission inventories for 2010 (ARPAV e Regione Veneto, 2015) reported that combustion in energy and transformation industries accounts for~72% of total SO 2 emissions in the Venice Province.…”
Section: Pmf Resultsmentioning
confidence: 68%
“…It has been reported that the probability of nucleation is increased by elevated SO 2 concentrations (e.g., Stanier et al, 2004) and a 13 year-long monitoring of airborne pollutants conducted in Mestre (Masiol et al, 2014b) reported evident peaks of SO 2 for winds blowing from the industrial zone. A large influence of oil refineries and/or coal-fired power plants upon the particle number concentrations in the nucleation range have been observed in many parts of the world (e.g., Stevens et al, 2012;Cheung et al, 2012;Gonz alez and Rodríguez, 2013).…”
Section: Pmf Resultsmentioning
confidence: 99%
“…Anderson et al, 2005;Herndon et al, 2008;Kinsey et al, 2010;Mazaheri et al, 2009Mazaheri et al, , 2013Masiol and Harrison, 2014;Lobo et al, 2015Lobo et al, , 2012 as well as from other anthropogenic (e.g. Schneider et al, 2005;Chen et al, 2011;Cheung et al, 2012;Stevens et al, 2012;Kumar et al, 2013Kumar et al, , 2014Vu et al, 2015b) and natural (e.g. Kulmala et al, 1998;O'Dowd et al, 1998O'Dowd et al, , 1999Kulmala and Kerminen, 2008;Riccobono et al, 2014) sources.…”
Section: Warm Seasonmentioning
confidence: 99%